CAESALPINIA BONDUC (L.)ROXB AS A NOVEL DRUG HAVING HYPOGLYCEMIC EFFECT ON ALLOXAN INDUCED DIABETIC RATS - B.VARALAKSHMI; THIRUNETHIRAN KARPAGAM; M.BARANI (International Journal of Pharma and Bio Sciences, 2011)
Diabetes mellitus is a major endocrine disorder. Herbal treatments are becoming increasingly popular, as the herbal preparations have no or least side effects than synthetic hypoglycaemic drugs. Hence research has been focused on scientific evaluation of traditional hypoglycaemic drugs of plant origin. In our present study the methanolic extract of hyperglycaemic was investigated for its anti-hyperglycaemic activity at two different doses (100 mg/kg, 200mg/kg body weight hyperglycaemic on blood glucose, lipid profile and antioxidant levels in alloxan induced diabetic rats against standard drug Glibenclamide (600 µg/kg b.w). Results of biochemical estimations were reported as mean ± SD. It was conclude that from these studies the extract prepared from the leaves of Caesalpinia bonduc (L.)Roxb possess potential hypoglycaemic effects when compared with standard drug Glibenclamide. Even though both the concentrations showed varying degree of anti-hyperglycaemic activity, 200mg/kg b.w dosage showed better anti-hyperglycaemic activity.